Stress- and smoke free pregnancy study protocol: a randomized controlled trial of a personalized eHealth intervention including heart rate variability-biofeedback to support pregnant women quit smoking via stress reduction - Willeke van Dijk; Mirjam Oosterman; Imke Jansen; Wieke de Vente; Anja Huizink (BMC, 2021)
Abstract Background Maternal smoking and stress during pregnancy are associated with adverse health effects for women themselves and are risk factors for adverse developmental outcomes of the unborn child. Smoking and stress seem to be intertwined in various ways. First, the majority of smoking pregnant women is of lower socio-economic status, which is associated with higher levels of perceived stress. Second, smoking women often report to smoke because they feel stressed. Third, quitting smoking often increases perceived stress levels initially. Therefore, effective interventions are needed to support women with smoking cessation by reducing stress. The aim of this study is to test the effectiveness of an eHealth intervention on stress reduction and smoking cessation. Methods/design The Stress- and Smoke Free Start of Life (SSFSL) study is a randomized controlled trial (RCT) comparing a personalized eHealth intervention with a control condition. Inclusion criteria for the women are: (1) > 18 years of age, (2) < 28 weeks pregnant at recruitment, (3) currently smoking. Consenting participants will be randomly assigned to the intervention or control group. Participants allocated to the intervention group will receive an 8-week intervention delivered on their smartphone. The application includes psycho-education on pregnancy, stress, and smoking (cessation); stress-management training consisting of Heart Rate Variability-biofeedback; and a personalized stop-smoking-plan. Participants in the control condition will be invited to visit a webpage with information on pregnancy, stress, and smoking (cessation). Study outcomes will be collected via online questionnaires, at four timepoints: pre-intervention (baseline; t0), post-intervention (8 weeks + 1 day after t0; t1), follow up at two weeks after birth (t2), and follow up at three months after birth (t3). The primary outcome measure is self-reported smoking cessation. Secondary outcomes include daily self-reported number of cigarettes smoked, perceived stress, pregnancy experience, birth outcomes, and negative affectivity scores of the baby. Moreover, the mediating effect of stress reduction on smoking cessation will be examined, and possible moderators will be tested. Discussion If the eHealth intervention is effective in smoking cessation among pregnant smoking women, it can be implemented as a tool into the health care in the Netherlands. Trial registration Netherlands Trial Register, ID: NL8156 . Registered on 11 November 2019.